2002
DOI: 10.1034/j.1600-0773.2002.910406.x
|View full text |Cite
|
Sign up to set email alerts
|

Pien Tze Huang Protects the Liver against Carbon Tetrachloride‐Induced Damage

Abstract: Pien Tze Huang, a traditional Chinese medicine, has been extensively used as a therapeutic drug in the treatment of liver diseases. In this study, we have examined its ability to protect the liver from carbon tetrachloride (CCl 4 )-induced damage in the mouse. Histological observations revealed that CCl 4 treatment induced extensive degenerative changes in the hepatocytes surrounding the central veins of the liver. However, these changes were much reduced by more than 28% in mice fed with 0.5 mg of Pien Tze Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…The second parameter was even more important in that the effect was in a linear relationship as the dosage increased in the cancerous cell culture, suggesting that a specific anti-cancer activity of Pien Tze Huang might have been at work. It has been widely suggested in the literature of Chinese medicine that Pien Tze Huang would inhibit liver cancer cells (Lee et al, 2002). Here, we raised the possibility that it may also affect the survival of brain tumor cells in culture.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The second parameter was even more important in that the effect was in a linear relationship as the dosage increased in the cancerous cell culture, suggesting that a specific anti-cancer activity of Pien Tze Huang might have been at work. It has been widely suggested in the literature of Chinese medicine that Pien Tze Huang would inhibit liver cancer cells (Lee et al, 2002). Here, we raised the possibility that it may also affect the survival of brain tumor cells in culture.…”
Section: Discussionmentioning
confidence: 98%
“…Its main ingredients are musk (now replaced by artificial musk), calculus bovis (gallstone of the ox), snake's gall, and Tienchi (also known as Sanqi, the root of Panax notoginseng). In our previous study, we have shown that Pien Tze Huang could protect liver from carbon tetrachloride damage, which might lead to the development of hepatoma (Lee et al, 2002). In our present series of investigations on the possible effects of Pien Tze Huang of the central nervous system, we first studied the in vitro anti-cancer activity of Pien Tze Huang on neuroblastoma cells (SH-SY5Y) as compared with normal fibroblasts in culture (NIH-3T3), using a cell survival test, the 3-(4,5-dimethylthiazol-2-yl)-2,2-diphenyltetrazolium bromide (MTT) reduction test (Lü, Li, Yew, Rudd, & Mak, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Pien Tze Huang, a complex mixture of Panax notoginseng (PNS) (85%), snake's gall bladder (7%), cow bezoar (dried cattle gall bladder stones) (5%), and musk (3%) has long been produced in China, and it is also widely used by Chinese immigrants in the United States for fatty liver, chronic hepatitis, inflammatory diseases, and detoxification. 2 PNS belongs to Panax, the same genus as Asian ginseng. The root of PNS in traditional Chinese herbs is nextracted for analgesic and hemostatic regiments.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical practices have also shown that a number of TCMs exhibit antitumor activity, which provides a novel therapeutic strategy for cancer treatment (6). Pien Tze Huang (PZH) is a well-known TCM that was identified ~450 years ago and has been applied to the treatment of liver diseases, cancer, stroke and inflammation (7). Similar to a number of other TCMs, PZH contains numerous ingredients, including musk, calculus bovis, snake’s gall and tienchi.…”
Section: Introductionmentioning
confidence: 99%